OUTCOME IMPLEMENTATION AS A BOOSTER FOR PUBLIC ORGANIZATION PERFORMANCE ACHIEVEMENTS (STUDY AT BAPPELITBANGDA, EAST NUSA TENGGARA) - Permata Sari, Siska Intan; Muluk, Mujibur Rahman Khairul; Amirudin, Ahmad (Erudio Journal of Educational Innovation, 2024)
ABSTRACTThis paper discusses the importance of building outcome implementation as a driving force for achieving public organization with a case study at Bappelitbangda, East Nusa Tenggara. This paper explains that development planning consists of several stages: planning, implementation, control, and evaluation. Outcome implementation is the main focus in achieving the results required in regional development planning. This study uses the method of literature study. LAKIP is the output of the performance of public organizations, which is also a monitoring and evaluation tool that provides an overview of the extent to which government agencies achieve the goals set in the planning. The LAKIP results show good performance at Bappelitbangda in East Nusa Tenggara. In the context of outcomes, the expected results of the performance of public organizations are regional development which is then seen from the achievement of regional macro indicators in the Regional Development Work Plan (RKPD) East Nusa Tenggara in 2022. Development performance achievements reflect social, economic, or change in the desired environment. Next, the author discusses implementing outcomes to achieve desired results in public organizations. Focus on Outcomes enables a better evaluation of the effectiveness of programs and activities implemented. Public organizations can improve efficiency, effectiveness, and accountability by building the implementation of Outcomes. Studies and practice in other countries have provided evidence that implementation outcomes can enhance the performance of public organizations. In conclusion, it is essential to implement Outcomes as a driving force for achieving public organizations. Focus on Outcomes allows public organizations to achieve significant benefits or impact and improve efficiency, effectiveness, and accountability.